INCLUSÃO ESCOLAR: A ARTICULAÇÃO ENTRE EDUCAÇÃO ESPECIAL E O ENSINO REGULAR POR MEIO DO TRABALHO COLABORATIVO DOS PROFISSIONAIS - FRANCOS, IVANA CARLA CORDEIRO DA SILVA (2023)
This research aims to analyze the articulation of collaborative actions between the regent teachers and resource room teachers, through the joint construction of a Formative Didactic Experiment and its application to the students, with the purpose of reflecting on their learning in the face of a content. Some of the steps taken in this study were understanding the school reality and observing whether Collaborative Teaching can be articulated in the school environment, organizing conversation circles between resource room teachers and regent teachers, in order to articulate, through collaborative action, the construction and the application of the Formative Didactic Experiment and investigate the actions that can be built collaboratively among the professors, with a focus on the students' learning. Therefore, this study is characterized as qualitative and the conversation wheel was used as a method for data collection, through studies with the theoretical framework about the Historical-Cultural Theory, Developmental Theory, Collaborative Teaching and Assessment in the Inclusive Context. From the data analysis it was possible to perceive the importance of reorganizing the school context. Providing moments of discussion and reflection about student learning, through collaborative teaching among teachers. Finally, through the entire study carried out and the pedagogical suggestions presented, it was possible to confirm that the knowledge and experiences of each professional are equally valued, since it is understood that the sum and exchange of differentiated knowledge between them will enhance the construction of more inclusive practices. Another point that was listed in this study is the importance of the management team, which becomes essential for the effectiveness of this process, reorganizing the school context so that collaborative teaching becomes effective in the daily life of the school.